Using Audio-Visual Media to Improve The Religious Character of Children In Fathina Kindergarten, Majene Regency, Indonesia - St. Maria Ulfah (AT-TURATS, 2022)
At present, the learning conditions in instilling character in students at Fatinah Kindergarten are not maximized, so what happens to the students has not applied the expected character values. This study aimed to describe efforts to improve religious character in Kindergarten children by using audio-visual media. Class Action Research (CAR) is operated to answer several problem formulations in this study. Data was collected using observation sheets and then analyzed qualitatively. It was conducted at Kindergarten Group B Fathina Kindergarten, Majene Regency, West Sulawesi, Indonesia. The results of this study indicate that there has been an increase in religious character, as seen from the percentage score from cycle I to cycle II. Thus it can be concluded that the planning and implementation of learning in improving the religious character of children through audio-visual media.